Prevalence and predictors of spontaneous bacterial peritonitis: does low zinc level play any role? - Asmaa N Mohammad; Laila M Yousef; Hamdy S Mohamed (Wolters Kluwer Medknow Publications, 2016)
Introduction Spontaneous bacterial peritonitis (SBP) is a frequent and life-threatening complication of cirrhosis. Several large studies have identified additional risk factors for the development of SBP. Zinc deficiency has been found to be frequent in cirrhotic patients. Aim of the work The aim of the present study was to evaluate the frequency, possible risk factors and the role of zinc in the development of first-time and recurrent SBP. Methodology A total of 176 cirrhotic ascetic patients admitted to the Hepatology Department in Sohag University Hospital were enroled in the study. SBP peritonitis was diagnosed through history-taking and through examination and laboratory investigations, including ascetic fluid study and the detection of serum zinc level. Results Of the 176 cirrhotic patients, SBP was diagnosed in 54 (31%); in total, 40 patients (23%) had single and 14 (8%) had recurrent episodes of SBP. Out of the 23 studied clinical and laboratory variables, we found that the prolonged use of proton pump inhibitor (PPI) (P = 0.001), lower prothrombin concentration (P = 0.03), ascetic protein level less than or equal to 1 g/dl (P < 0.0001) and zinc deficiency (P = 0.001) were independent risk factors for the development of SBP in cirrhotic patients; using multivariate analysis, only low protein in ascites less than or equal to 1 and low zinc status were predictors of SBP. Conclusion In our study, the frequency of SBP was 31%; overall, 23% of the patients had first-episode and 8% had recurrent SBP. The use of PPI, low platelet count, ascetic protein content and zinc deficiency were the predictors for the development of SBP; only low protein in ascites less than or equal to 1 and low zinc status were independent predictors of SBP.